2005
DOI: 10.1080/09513590500099305
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone and human placental lactogen inhibit leptin secretion on cultured trophoblast cells from human placentas at term

Abstract: The placenta is an important source of leptin production that contributes to the state of hyperleptinemia observed in pregnant women. Moreover, the synthesis of leptin and its receptors by syncytiotrophoblast cells suggests a potential paracrine or autocrine action of leptin in the placenta. In the present study we examined the effect of gestational hormones, human chorionic gonadotropin (hCG), human placental lactogen (hPL), progesterone and estradiol, on in vitro leptin release by human term trophoblast cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 14 publications
0
11
0
2
Order By: Relevance
“…Our results clearly demonstrated that pathologies, such as endometriosis and polycystic ovary syndrome (37,40). Different data reveal that leptin gene expression is regulated by P in human adipose tissue and in human placenta (41)(42)(43). Thus, it cannot be ruled out that P may regulate leptin expression in the human endometrium.…”
Section: Discussionmentioning
confidence: 48%
“…Our results clearly demonstrated that pathologies, such as endometriosis and polycystic ovary syndrome (37,40). Different data reveal that leptin gene expression is regulated by P in human adipose tissue and in human placenta (41)(42)(43). Thus, it cannot be ruled out that P may regulate leptin expression in the human endometrium.…”
Section: Discussionmentioning
confidence: 48%
“…The increase in serum leptin and ghrelin level was greater in the women with SPE than that of the MPE group. Parallel increased umbilical venous and arterial leptin and ghrelin concentrations may partly originate from the placenta (14,(28)(29)(30)(31)(32)(33)(34)(35)(36). Ghrelin, leptin and their mRNAs are present in rat (31) as well in human placenta (30).…”
Section: Discussionmentioning
confidence: 99%
“…Women with normal pregnancy show elevated level of leptin during the second trimester of pregnancy while its level decreases rapidly at postpartum period (13). Leptin is also produced in human placenta and in syncytiotrophoblasts at maternal-fetal interface (14). It contributes to the regulation of fetal growth and development and plays a role in the successful outcome of human pregnancy (15).…”
mentioning
confidence: 99%
“…In late pregnancy when placental progesterone production is at its height, progesterone has been reported to inhibit leptin secretion by human placental cells in culture (Coya et al, 2005). On the other hand, leptin always led to an inhibitory effect on progesterone secretion (Cameo et al, 2003).…”
Section: Progesteronementioning
confidence: 99%